Starch contamination landscapes in field archaeology: Olduvai Gorge, Tanzania. (20th March 2017) - Mercader, Julio; Abtosway, Matthew; Baquedano, Enrique; Bird, Robert W.; Díez‐Martín, Fernando; Domínguez‐Rodrigo, Manuel; Favreau, Julien; Itambu, Makarius; Lee, Patrick; Mabulla, Audax; Patalano, Robert; Pérez‐González, Alfredo; et al.
Abstract : No agreement on what constitutes a safe and reproducible anticontamination protocol exists for ancient starch research. Protocols applied to laboratory work may represent 'symptomatic treatment' only, as contamination of archaeological materials in the field may be more extensive than realized. This paper is the first systematic study on the impact that modern starches from surface and buried soils, windborne dispersal, human motion, excavation techniques and toolkits, and field attire has on archaeological sample quality. The study area is Olduvai Gorge, Tanzania. We identify seven starch types (discrete granules, n = 788) that embody the starch contamination landscape for the region. This study also demonstrates the various diagenetic changes that buried starch granules undergo in a short time, such as cavitation, fissuring, disruption and gelatinization. There are significant differences in morphotype class representation between the topsoil starches and those collected deeper below ground at excavated sites. Diagenetically transformed granules from underground storage organs dominate in soils, while native starches from cereal endosperm (Panicoideae and Triticeae) abound above ground in airborne samples. Furthermore, we illustrate how lithic samples excavated under standard field conditions can be contaminated, and that when a sample is compromised during excavation, it may be impossible to distinguish between target and introduced starches, especially when granules are identical or morphologically similar. The paper provides field recommendations to control false positives.